Faktor-Faktor yang berpengaruh pada Keberlanjutan Usaha Biro Jasa Perjalanan Haji dan Umrah - Prihanto, Hendi; Damayanti, Prisila (Research Center and Case Clearing House PPM School of Management, 2022)
This study aims to explain the influence of business prospects, image, promotion, assurance, and trust of prospective pilgrims as factors that influence the sustainability of the Hajj and Umrah travel service bureau business. The research population is prospective hajj and umrah pilgrims who have associations with a number of travel companies in the East Cilandak region. Samples were randomly selected and determined based on the time of meeting activities often carried out by the association formed by the prospective congregation. They are collecting data using a questionnaire that was analyzed by testing the validity, reliability, descriptive statistical test, hypothesis testing, and coefficient of determination. The results of the study state that business prospects, promotions, and trust have a significant positive effect on business sustainability, while guarantees have no effect. Moderation hypothesis test states that trust does not moderate to strengthen image and promotion, while confidence moderates perceptions and strengthens assurance towards business sustainability. The limitation of the study is that the sample used has not been able to conclude the results of the study as a whole due to incomplete sampling in the population area because it is limited to one area. Nevertheless, the implications of the research are contributing to the concept of developing the factors that affect business continuity, improving business strategies, and increasing revenue for Hajj and Umrah travel agents.